Integrating Genre-Based Approach and Differentiated Instruction to Improve Seventh Graders’ Descriptive Writing Skills in a Junior High School in Kediri - Masyhudianti, Ummy Khoirunisya' (JOM, 2025)
This study aimed to delve whether integrating the Genre-Based Approach (GBA) with Differentiated Instruction (DI) can improve writing skills among seventh-grade students in a Junior High School in Kediri, Indonesia. The research applied a Classroom Action Research (CAR) design, which included two cycles of planning, acting, observing, and reflecting. The findings indicate that the implementation of GBA combined with DI enhanced students’ writing proficiency, particularly in the production of descriptive texts. The post-test results of Cycle 2 indicated that 81.25% of students’ mean score reached 77.8, surpassing the minimum passing grade (KKM) of 75 and demonstrating a substantial improvement compared to the mean score obtained in Cycle 1 (62). Additionally, qualitative data showed that students' engagement, enthusiasm, and attitudes toward English writing improved, as they became more involved in class discussions, writing exercises, and collaborative activities. The study further highlights that the integration of DI with GBA addresses the diverse learning needs of students, fostering a more interactive and student-centered learning environment. The research contributes to the growing body of literature on the application of GBA and DI in EFL contexts and suggests that these approaches can be used to improve writing skills in junior high school students. Future research could examine the long-term effects of this approach, its applicability to different writing genres, and the potential integration of digital platforms to enhance learning.